EVALUASI STRUKTUR DAN SKALA UPAH PADA UMKM STUDIO FOTO XYZ MENGGUNAKAN METODE OVERLAPPING - Barokah Dwi Rahmayani; Bintu Tsani Haunaniswah; Novaldi Ramadhani; Reyhan Fadila Hidayatusadikin (Jurnal Pijar, 2026)
The lack of structured compensation systems has become a significant challenge for the sustainability of Micro, Small, and Medium Enterprises (MSMEs), particularly in the photography sector. Unclear salary structures often lead to internal inequity, decreased employee motivation, and high employee turnover. This study aims to analyze and redesign the salary structure at Studio Foto XYZ MSME using a salary mapping approach with the overlapping method. The research employs a descriptive qualitative method with data collected through in-depth interviews, observations, and documentation studies. The data were critically analyzed to map current salary positions against market standards and internal equity. The results indicate that the implementation of salary mapping using the overlapping method can create a more flexible, transparent, competitive, and equitable salary structure. The proposed compensation structure is expected to improve employee retention while supporting operational cost efficiency within the MSME. This study provides practical contributions for MSME owners in optimizing adaptive compensation systems without implementing overly bureaucratic structures.